Treatment of common warts with the immune stimulant Propionium bacterium parvum Tratamento das verrugas vulgares com o imunoestimulante Propionium bacterium parvum - Nilton Nasser (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Warts are epithelial proliferations in the skin and mucous membrane caused by various types of HPV. They can decrease spontaneously or increase in size and number according to the patient's immune status. The Propionium bacterium parvum is a strong immune stimulant and immune modulator and has important effects in the immune system and it is able to produce antibodies in the skin. OBJECTIVE: To show the efficacy of the Propionium bacterium parvum in saline solution in the treatment of skin warts. METHODS: A randomized double-blind study. Twenty patients with multiple warts were divided into two groups: one received 0,1ml intradermal injection of placebo solution in just one of the warts and the other received 0,1 ml of saline solution of Propionium bacterium parvum, one dose a month, for 3 to 5 months. RESULTS: Among the 20 patients who participated in the study, ten received the placebo and ten received the saline solution with Propionium bacterium parvum. In 9 patients treated with the Propionium bacterium parvum solution the warts disappeared without scars and in 1 patient it decreased in size. In 9 patients who received the placebo no change to the warts was observed and in 1 it decreased in size. CONCLUSIONS: The immune modulator and immune stimulant Propionium bacterium parvum produced antibodies in the skin which destroyed the warts without scars, with statistically significant results (P<0,001), and cured 90 % of the patients. We suggest the use of the immune stimulant in the treatment of warts. FUNDAMENTOS: Verrugas são proliferações epiteliais na pele e mucosas causadas por diversos tipos de HPV. Elas podem involuir espontaneameme ou aumentar em número e tamanho de acordo com estado imunitário do paciente. O Propionium bacterium parvum é urn potente imunoestimulador e imunomodulador e tem efeitos importantes no sistema imune e é capaz de produzir anticorpos na pele. OBJETIVO: Mostrar a eficácia do Propionium bacterium parvum diluído em solução salina no tratamento de verrugas cutâneas. MÊTODOS: Estudo duplo-cego randomizado. Vinte pacientes com verrugas múltiplas foram divididos em dois grupos, um recebeu aplicação intradérmica do placebo em uma (1) única verruga e o outro da solução salina com Propionium bacterium parvum, uma dose por mês por 3 a 5 meses. RESULTADOS: Dos 20 pacientes do estudo, dez receberam placebo e 10 de solução salina com Propionium bacterium parvum. Dos pacientes tratados com Propionium bacterium parvum nove (9) foram curados e um teve diminuição das lesões. Do grupo do placebo nove (9) não apresentaram alterações e 1 (um) apresentou diminuição das lesões. CONCLUSÔES: O imunomodulador e imunoestimulador Propionium bacterium parvum produz anticorpos na pele que destroem as verrugas sem cicatrizes e mostrou uma significância de P<0,001, com cura de 90% dos pacientes submetidos à terapia. Sugerimos a utilização de imunoestimulante para o tratamento de verruga vulgar.